High-resolution shotgun proteomics reveals that increased air [CO2] amplifies the acclimation response of coffea species to drought regarding antioxidative, energy, sugar, and lipid dynamics - Marques, Isabel (2022)
Funding Information: This work received funding support from the European Union's Horizon 2020 research and innovation program (grant agreement No 727934 , project BreedCAFS), and from national funds from Fundação para a Ciência e a Tecnologia, I.P. (FCT) , Portugal, through the project PTDC/ASP-AGR/31257/2017 , and the research units UIDB/00239/2020 ( CEF ), and UIDP/04035/2020 (GeoBioTec) and under the Scientific Employment Stimulus - Individual Call (CEEC Individual) - 2021.01107.CEECIND/CP1689/CT0001 (IM) . Fellowships from the Conselho Nacional de Desenvolvimento Científico e Tecnológico, Brazil (CNPq) , (to F.M. DaMatta and F.L. Partelli), and Fundação de Amparo à Pesquisa do Estado de Minas Gerais, Brazil (FAPEMIG, projects CRA-RED-00053-16 and APQ 01512-18 , to F.M. DaMatta) are also greatly acknowledged. Publisher Copyright: © 2022 Elsevier GmbH